Alpiscorpius victori sp. n. from the Murat Mountain, Kütahya and Uşak Provinces, Turkey (Scorpiones: Euscorpiidae) - Yağmur, E. A. (Publishing House "Akademperiodyka" of the National Academy of Sciences of Ukraine, 2025)
A new scorpion species, Alpiscorpius victori sp. n., is described from Mount Murat, located in Kütahya and Uşak Provinces in the Aegean Region of western Turkey, based on morphological evidence. The species is classified within the genus Alpiscorpius Gantenbein et al., 1999, due to the presence of three trichobothria in the em series on the external surface of the pedipalp patella. With the addition of this species, the number of known species in the family Euscorpiidae rises to 24, while the genus Alpiscorpius now includes six species in Turkey.